2019
DOI: 10.1111/zph.12617
|View full text |Cite
|
Sign up to set email alerts
|

Chinese poultry farmers' decision‐making for avian influenza prevention: a qualitative analysis

Abstract: Poultry farmers faced dual risk when mutant avian influenza (AI) virus showed the zoonotic characteristics. A/H5N1 and A/H7N9 were two dominant AI virus strains that have captured the attention of the public over the years for they have been reported to bring about greater loss to poultry and human, respectively. Previous studies mainly used quantitative methods investigating either the means that poultry farmers adopted for protecting their poultry against A/H5N1 infection or the poultry farmers' self‐protect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…To begin with, the previous studies fundamentally focussed on the prevention and control of diseases such as Malaria, AIDS, 1 West Nile, Dengue, Zika, and Chikungunya ( Cui et al, 2019 ; Omodior et al, 2018 ; Przybyla et al, 2019 ; Raude et al, 2019 ; Xiaoliang et al, 2016 ). The first group of researches focussed on the epidemiology of diseases like Malaria, Dengue, and AIDS ( Bryant-davis et al, 2016 ; Cui et al, 2019 ). The second group of researches was based on surveys and their interpretation through the response rate of certain variables on epidemic prevention ( Baghbanzadeh et al, 2020 ; Sued et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…To begin with, the previous studies fundamentally focussed on the prevention and control of diseases such as Malaria, AIDS, 1 West Nile, Dengue, Zika, and Chikungunya ( Cui et al, 2019 ; Omodior et al, 2018 ; Przybyla et al, 2019 ; Raude et al, 2019 ; Xiaoliang et al, 2016 ). The first group of researches focussed on the epidemiology of diseases like Malaria, Dengue, and AIDS ( Bryant-davis et al, 2016 ; Cui et al, 2019 ). The second group of researches was based on surveys and their interpretation through the response rate of certain variables on epidemic prevention ( Baghbanzadeh et al, 2020 ; Sued et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…We identified that the availability information on HPAI played an important role in the farmers' decision-making to implement HPAI prevention and control measures for all three chicken production systems. Similarly, Toma, Stott, Heffernan, Ringrose, and Gunn (2013) found that the provision of biosecurity information had a positive impact on farmers' biosecurity behaviour while Cui et al (2019b) also observed that information on AI disseminated through TV, web news and chats and via conversations between chicken farmers influenced the implementation of HPAI preventive measures. Unfortunately, farmers with different levels of intensification are often provided with similar advice on disease management.…”
Section: Discussionmentioning
confidence: 98%
“…Different studies highlighted that the likelihood of implementing AI prevention and control measures is depended on farmer's perception on the susceptibility of birds to AIV infection, the consequences of the disease, the benefits of implementing actions, any constraints or barriers to the implementation of those actions and sources of information that may influence individuals' perceptions (Cui, Liu, Ke, & Tian, 2019a;Cui, Wang, Ke, & Tian, 2019b;Glanz & Bishop, 2010;Glanz, Rimer, & Viswanath, 2008;Høg et al, 2018;Rimi et al, 2017). These factors towards the implementation of AI prevention and control measures will likely differ between backyard, commercial broiler, and commercial layer farmers, as farm management practices, production cycles, flock sizes as well level of education of flock owners differ between these three production systems (Cui, Liao, Lam, Liu, & Fielding, 2017;Cui & Liu, 2016;Jemberu et al, 2015).…”
Section: Attitudes Behaviours and Practices Of Backyard And Commercimentioning
confidence: 99%
See 2 more Smart Citations